Hydroponics – An Overview - Debangshi, Udit (Chronicle of Bioresource Management, 2021)
Soil-based agriculture is now facing major challenges due to urbanization, industrialization and environmental degradation etc. Among different problems, the most important one is the decline in per capita land availability. With 6 billion people on earth, the per capita land availability is currently 0.25 hectares and by 2050 it will be 0.16 hectares. Climate change along with urbanisation and industrialization magnifies this negative impact. To counteract these threats, hydroponics has emerged as a viable option which is currently gaining popularity around the world due to its efficient resource management. Hydroponic farms offer a viable solution towards a more sustainable food production while avoiding hazardous chemicals due to controlled environments and strict certification laws. Far from being a dream, hydroponic farming is already integrated into sustainable agriculture in order to meet rising global food demand.